Failure to Rescue as a Quality Improvement Approach in Transplantation: A First Effort to Evaluate This Tool in Pediatric Liver Transplantation. Issue 4 (April 2016) - Cramm, Shannon L.; Waits, Seth A.; Englesbe, Michael J.; Bucuvalas, John C.; Horslen, Simon P.; Mazariegos, George V.; Soltys, Kyle A.; Anand, Ravinder; Magee, John C.
Abstract : Background: Significant intercenter variation exists in mortality and death-censored graft loss (DCGL) after transplantation. Failure to rescue (FTR, death after a major complication) is an emerging tool in quality improvement and may underlie this variation. This study is the first effort to investigate the relationship between FTR and outcomes in transplantation to assess its utility in care improvement. Methods: Using the Studies of Pediatric Liver Transplantation database, we identified 2330 children undergoing primary liver transplants at 21 centers. Centers were ranked by risk-adjusted mortality and sorted into tertiles. We then compared mortality, complications, and FTR across tertiles. Results: Overall mortality was 4.9%, ranging from 1.4% to 8.1% in the low and high mortality tertiles ( P < 0.01). The low mortality tertile had significantly lower rates of complications (30.9% vs 38.5% and 40.4%, P < 0.01) as well as FTR (4.6% vs 9.9% and 14.3%, P < 0.01). A similar trend was seen in the DCGL analysis. Conclusions: Our results demonstrate that although centers with higher mortality and DCGL have more frequent major complications, they exhibit 3-fold the rate of FTR. Efforts to standardize perioperative care, and thus minimize FTR, will have value to pediatric liver transplantation recipients. This preliminary study indicates that FTR may provide a useful quality improvement tool for the field of transplantation and warrants further investigation. Abstract : The authors present the first analysis of "failure to rescue" in pediatric liver transplantation as a quality metric. This concept evaluates the ability of the team and the field strength to overcome the impact of complications achieving a successful overall outcome. This report from the SPLIT registry is an important contribution to understanding the components of quality in liver transplantation.